A large scale hearing loss screen reveals an extensive unexplored genetic landscape for auditory dysfunction. Issue 1 (December 2017) - Bowl, Michael; Simon, Michelle; Ingham, Neil; Greenaway, Simon; Santos, Luis; Cater, Heather; Taylor, Sarah; Mason, Jeremy; Kurbatova, Natalja; Pearson, Selina; Bower, Lynette; Clary, Dave; et al.
Abstract The developmental and physiological complexity of the auditory system is likely reflected in the underlying set of genes involved in auditory function. In humans, over 150 non-syndromic loci have been identified, and there are more than 400 human genetic syndromes with a hearing loss component. Over 100 non-syndromic hearing loss genes have been identified in mouse and human, but we remain ignorant of the full extent of the genetic landscape involved in auditory dysfunction. As part of the International Mouse Phenotyping Consortium, we undertook a hearing loss screen in a cohort of 3006 mouse knockout strains. In total, we identify 67 candidate hearing loss genes. We detect known hearing loss genes, but the vast majority, 52, of the candidate genes were novel. Our analysis reveals a large and unexplored genetic landscape involved with auditory function. The full extent of the genetic basis for hearing impairment is unknown. Here, as part of the International Mouse Phenotyping Consortium, the authors perform a hearing loss screen in 3006 mouse knockout strains and identify 52 new candidate genes for genetic hearing loss.